Rosmarinic acid attenuates TNF-α induced cardiomyocyte injury via regulating miR-344a-3p: Rosmarinic acid protects CMs from TNF-α induced injury - Zhang, Jun; Du, Yingqiang; Li, Yafei (Cellular and Molecular Biology, 2024)
To investigate whether rosmarinic acid protects cardiomyocytes from inflammatory damage through miRNAs, high-throughput sequencing and bioinformatics analysis were performed to identify TNF-α-induced inflammatory damage in cardiomyocytes and miRNAs differentially expressed in TNF-α-induced inflammatory injury in cardiomyocytes, and the bioinformatics analysis shown that the expression levels of 10 miRNAs were significantly up-regulated, and the expression levels of 6 miRNAs were significantly down-regulated. Among them, the expression level of miR-344a-3p was significantly up-regulated in the experimental group, while the expression level of miR-449c-5p was significantly down-regulated in experimental group of cells. The target genes of miR-344a-3p and miR-449c-5p were CCR1 and ATP2B4 respectively. The luciferase reporter system showed that luciferase activity in the WT-CCR1+miR-344a-3p mimic group was significantly decreased, and the expression of CCR1 was significantly decreased at mRNA and protein level after miR-344a-3p was transfected into H9C2 cells, indicating that TNF-α-induced inflammatory injury in cardiomyocytes, rosmarinic acid may up-regulate the expression of miR-344a-3p, thereby inhibiting the expression of CCR1 and ultimately protecting the cardiomyocytes from inflammatory damage. Thus, we thought that CCR1 might be a new therapeutic target for cardiomyocyte injury.